SATISFACTION OF QUALIFICATION REQUIREMENTS OF EMPLOYERS APPLIED TO SOFTWARE ENGINEERS IN THE PROCESS OF TRAINING AT HIGHER EDUCATIONAL INSTITUTIONS - Vladislav Kruhlyk (Kherson State University, 2017)
In the article, based on the analysis of the problems of the professional training of software engineers in higher educational institutions, was shown that the contents of the curricula for the training of software engineers in basic IT specialties in higher education institutions generally meet the requirements to them at the labor market. It is stated that at the present time there are certain changes in the job market not only in the increasing demand for IT professionals but also in the requirements settled for future specialists. To scientists' opinion, at present there is a gap between the level of expectation of employers and the level of education of graduates of IT-specialties of universities. Due to the extremely fast pace of IT development, already at the end of the studies, students' knowledge may become obsolete. We are talking about a complex of competencies offered by university during training of specialist for their relevance and competitiveness at the labor market. At the same time, the practical training of students does not fully correspond to the current state of information technology. Therefore, it is necessary to ensure the updating of the contents of the academic disciplines with the aim of providing quality training of specialists.